The importance of building the fiscal space to restore the external economic balance in Algeria - Hamidat , Amar; Bouhoreira , Abbas (Dirassat Journal Economic Issue, 2024)
The study aimed to determine the importance of building fiscal space in Algeria in order to restore external economic balance. The paper is based on economic analysis and statistical analysis of dynamic models (VAR). This paper concluded that, Algeria has exceptional opportunities for the financial reset of public finances (internal balance) and the balance of payments ( External balance) and reduce the deficit in public finances and maintain the state of external balance of payments. Accordingly, the paper recommended the importance of public financial governance, especially public spending towards the most efficient economic sectors, as well as the importance of a balanced growth strategy commensurate with the economic and social situation in Algeria for economic diversification.